The Trichodesmium microbiome can modulate host N2 fixation - Kyle R. Frischkorn; Mónica Rouco; Benjamin A. S. Van Mooy; Sonya T. Dyhrman (Limnology and Oceanography Letters, 2018)
Abstract Trichodesmium is a marine, diazotrophic cyanobacterium that plays a central role in the biogeochemical cycling of carbon and nitrogen. Colonies ubiquitously co‐occur with a diverse microbiome of heterotrophic bacteria. We show that manipulation of the microbiome with quorum sensing acyl homoserine lactones (AHLs) significantly modulated rates of N2 fixation by Trichodesmium collected from the western North Atlantic, with positive and negative effects of varied magnitude. Changes in Trichodesmium N2 fixation did not correlate with changes in microbiome composition or geochemistry. With AHL addition, a subset of the significantly differentially expressed genes was related to known quorum sensing responses in model bacteria. However, there was little overlap in specific microbiome transcriptional responses to AHL addition between stations. Overall, these host‐microbiome interactions reflect a complex interplay of biotic and environmental factors that together form an overlooked mechanism modulating Trichodesmium N2 fixation.